PENYULUHAN PENERAPAN PENGERING PORTABLE BUAH PINANG BERBASIS PANEL SURYA DI PEUNARON LAMA, ACEH TIMUR, INDONESIA - Harmawan, Tisna; A. Mustaqin, Wendy; Andi Fadly, Teuku (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
Betel nut or pinang palm’s (Areca catechu L.) seed is one of the most important source of income for the people in Peunaron Lama Village, Peunaron Subdistrict, Aceh Timur Regency, Aceh Province, Indonesia. A training to a local group to introduce the function and use of a donated solar-panel powered drier was done in June 2022. The training program is a part of community engagement to increase the effectivity of betel nut drying. This aimed to increase the income for the local community in the village who depend much on the production of the dry betel nut seeds. The local people who participate in training are very interested and learn with enthusiast during the training and even ask for further modification of the equipment to adjust the specific needs. With the success training program, further evaluations are needed to improve the effectivity of solar-panel powered drier especially to the quality of the produced dry betel nut seeds.